Perbandingan Pengaturan Perlindungan Saksi Tindak Pidana Pencucian Uang - Ahmad Dahlan; Usman Usman; Herry Liyus (Fakultas Hukum, Universitas Jambi, 2021)
This article aims to find out and analyze the similarities and differences in the protection of witnesses to the crime of money laundering in law of Indonesia and Malaysia. The research method used is normative juridicial. The data collection techniques used are secondary data collection that carried out by library research to collect and compile data related to the problem under study, by taking an inventory and studying laws and regulations, books , writings and documents related to the issues that the author examined. The data analysis techniques with content analysis. The results obtained from this study are that the arrangements for witness protection in the Money Laundering Law in Indonesia and Malaysia are different. protected subjects (namely: witness, the reporter, the family of the witness/reporter) as well as the broader arrangements in Indonesia as well as in its implementation special protection arrangements have been made in the PP and Decree of the Chief of the Indonesian National Police. Protection provided at all stages of case examination, in the form of special and legal protections. Whereas in Malaysia, the implementation only refers to the provisions of witness protection. Protection only takes the form of legal protection provided to reporting witnesses only, so that during the trial process , a witness has no protection. Abstrak Artikel ini bertujuan untuk mengetahui dan menganalisis persamaan dan perbedaan perlindungan saksi tindak pidana pencucian uang di Indonesia dan Malaysia. Jenis penelitian yuridisÂ normatif. Teknik pengumpulan data yang digunakan yaitu melalui pengumpulan data-data sekunder. Teknik pengumpulan data dilakukan dengan studi kepustakaan untuk mengumpulkan dan menyusun data yang berhubungan dengan masalah yang diteliti, dengan cara menginventarisasi dan mempelajari peraturan perundang- undangan, buku-buku, tulisan-tulisan dan dokumen yang berhubungan dengan masalah yang penulis teliti. Teknik analisis data dengan analisis isi (content). Hasil yang diperoleh dari penelitian ini yaitu bahwa pengaturan perlindungan saksi di Indonesia dan Malaysia adalah berbeda. Dalam hal subjek yang dilindungi (yaitu: saksi, pelapor, keluarga saksi/pelapor). Perlindungan yang diberikan pada semua tahap pemeriksaan perkara, dalam bentuk perlindungan khusus dan hukum. Sedangkan di Malaysia, pelaksanaanya hanya merujuk pada ketentuan perlindungan saksi. Perlindungan hanya berupa perlindungan hukum yang diberikan kepada saksi pelapor saja, sehingga dalam selama proses persidangan, seorang saksi tidak mendapat perlindungan.